Celebrating fifteen years of Jurnal Rekayasa Proses - Budhijanto, Wiratni (Jurnal Rekayasa Proses, 2022)
The year 2022 marks the fifteen-year service of Jurnal Rekayasa Proses since its first edition in 2007. Fifteen years is a very long period to learn to manage a scientific journal and establish this journal's unique characteristics. Since its first issue, Jurnal Rekayasa Proses is expected to become a communication platform between academicians and industrial practitioners in scientific publication format. Jurnal Rekayasa Proses is an interface to introduce state-of-the-art innovation from the laboratory benches to the industrial application. On the other hand, it also updates the researchers in universities and institutions about the real problems in the industry. Therefore, amid journals' euphoria to pursue journal quality status through an international indexation platform, Jurnal Rekayasa Proses opts to hold high its vision as the national scientific communication bridge between academicians and industrial practitioners to establish the flagship technology of Indonesia synergically. The requirement of international indexation, especially on the number of foreign countries' origins of the authors, is not entirely relevant to the domestic orientation of Jurnal Rekayasa Proses. Therefore, Jurnal Rekayasa Proses guaranteed its scientific quality through the national accreditation system for a scientific journal and has been accredited as Sinta 2 since 2018. For this achievement, Jurnal Rekayasa Proses owed to all previous editor-in-chief and managing editors, Prof. Hary Sulistyo, Almarhumah Dr. Siti Syamsiah, Dr. Sholeh Ma’mun, Dr. Indra Perdana, Dr. Teguh Ariyanto, dan Dr. Himawan Tri Bayu Murti Petrus, and the Heads of Department Prof. I Made Bendiyasa, Prof. Suryo Purwono, Dr. Moh. Fahrurrozi, Dr. Muslikhin Hidayat, and Dr. A. Tawfiequrrahman Yuliansyah. Many thanks go to our best friends in various universities and research institutions who have voluntarily spent their priceless time and energy serving as reviewers and the editorial board of Jurnal Rekayasa Proses. We also would like to extend our gratitude to the Faculty of Engineering and the Publisher and Publication Board Universitas Gadjah Mada for all of the support and facilities to improve the quality of Jurnal Rekayasa Proses during the last fifteen years. As a special commemoration of the fifteen years of Jurnal Rekayasa Proses' existence, significant changes are ongoing in several aspects of the journal. The first stage of Jurnal Rekayasa Proses transformation in Edition 1 Volume 16 is the new journal theme with a more comfortable format for reading and linking to the references. We also modified the official colours by incorporating a shade of green as a symbol of the sustainability era in all areas, including process engineering. The orange color is maintained in the journal theme color palettes because this color very well represents the journal’s soul: warm, high-spirited, optimistic, confident, and friendly in expanding the network of friendship. More modifications will take place gradually to accommodate the readers' expectations and keep up with the fast-changing world. We warmly thank Siti Nurleily Marliana (Lelly) and Joaquim Baeta (Alex) for the excellent coaching in this journal transformation. We are thankful for all steps we have been guided, starting from the brainstorming to determine the journal theme and the tedious process of designing the article template in LaTeX. Finally, we completed the many steps of establishing the new look of the journal that you would enjoy in this issue forward. On top of all the technical details, we highly appreciate Lelly and Alex for inspiring us to manage a scientific journal passionately for one goal: perfection in the documentation and dissemination of the science for a broader audience. To wrap up, we invite you to enjoy our "Fifteen Year Birthday Edition" of Jurnal Rekayasa Proses. We hope that in the future, Jurnal Rekayasa Proses will grow better along its learning curve to serve the scientific exchanges between academicians and industrial practitioners to achieve a mutual goal of an innovative and resilient Indonesia.